The Role of Agents and Brokers in the Market for Health Insurance. Issue 1 (6th December 2016) - Karaca‐Mandic, Pinar; Feldman, Roger; Graven, Peter
Abstract: Health insurance markets in the United States are characterized by imperfect information, complex products, and substantial search frictions. Insurance agents and brokers play a significant role in helping employers navigate these problems. However, little is known about the relations between the structure of the agent/broker market and access and affordability of insurance. This article aims to fill this gap by investigating the influence of agents/brokers on health insurance offering decisions of small firms, which are particularly vulnerable to problems of financing health insurance. Using a unique membership database from the National Association of Health Underwriters together with a nationally representative survey of employers, we find that small firms in more competitive agent/broker markets are more likely to offer health insurance and at lower premiums. Moreover, premiums are less dispersed in more competitive agent/broker markets.